Ear symptoms in patients with orofacial pain and dysfunction ‐ An explorative study on different TMD symptoms, occlusion and habits - Christina Mejersjö; Nina Pauli (Wiley, 2021)
Abstract Objectives Ear symptoms coincident with TMD symptoms have been noticed for a long time. The aim was to investigate the relationship between reported ear symptoms in TMD patients and different TMD symptoms, dental occlusion, oral parafunction and habits. Material and methods Consecutive patients, ≥18 years of age and referred to a specialist clinic for orofacial pain and dysfunction during a three‐month period, were considered for the study. Patients with poor general or psychiatric health were excluded. One hundred thirty‐two patients were included and studied with regard to reported ear symptoms in relation to clinical dysfunction, occlusion, habits and subjective rating of their symptoms. A clinical examination was performed according to RDC/TMD and extended with occlusal factors, parafunctions and habits. Results Ear symptoms were reported by 72% of the TMD patients, with ear fullness in 49% as the most frequent symptom. The patients with ear symptoms were significantly older and proportionally more often females. Ear symptoms were significantly correlated to the subjective index, to myalgia (p = 0.003), decreased opening capacity (p = 0.01), TMJ pain (p = 0.02), parafunctions (p = 0.007), and some occlusal factor (p = 0.018-0.003). Muscle pain on palpation was significantly associated with ear fullness, and changed hearing and sensitivity to sound, on the same side (p < 0.005). Conclusions Ear symptoms are frequently reported by TMD patients. Concomitant ear symptoms are associated with oral parafunction and muscle pain on palpation on the same side as the ear symptoms.